The Power of Partisanship in Brazil: Evidence from Survey Experiments. Issue 1 (12th August 2013) - Samuels, David; Zucco, Cesar
<x xml:space="preserve">Abstract</x> To what extent do party labels influence individuals' policy positions? Much research has examined this question in the United States, where party identification can generate both in‐group and out‐group pressures to conform to a party's position. However, relatively little research has considered the question's comparative generalizability. We explore the impact of party labels on attitudes in Brazil, a relatively new democracy with a fragmented party system. In such an environment, do parties function as in‐groups, out‐groups, or neither? We answer this question through two survey experiments, one conducted on a nationally representative sample and another on a convenience sample recruited via Facebook. We find that both in‐ and out‐group cues shape the opinions of identifiers of Brazil's two main parties but that cues have no effect on nonpartisans. Results suggest that party identification can structure attitudes and behavior even in "party‐averse" electoral environments.